FIBROMA TRAUMÁTICO DA CAVIDADE ORAL - Santos, Ana Paula; Caçador, Maria; Capucho, Clara; Carvalho, Lucília; Ruah, Carlos; da Silva, Madeira (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.